FUNDAMENTAL ECONOMIC ANALYSIS OF VARIABLES AFFECTING THE U.S. DOLLAR EXCHANGE RATES AGAINST RUPIAH - Murdo, Yuri (Accounting, 2010)
This study aims to analyze the economic fundamental variables that affect the exchange rate of rupiah against U.S. dollar. Data used in this research is secunder data consisting of various editions of BPS.Metode analysis method is used autoregressive models are models of Partial Adjustment Model (PAM) results showed that the effect of money supply (M2) against the rupiah exchange rate against dollar. The greater the amount of money in circulation there will be a tendency of decreasing purchasing power of the rupiah against the dollar. M2 has positive influence on the exchange rate with dollar terhadfap short janka coefficient value 0.0136, which means if M2 increased by 1 point in the short-term rates rose 0.013. is in the long term increased by 0.0597. Effect of GDP against the rupiah rate against the dollar, the coefficient PDINA shows the number of 0, 0361, it has a meaning if the National Income increased by I unit, the rate fell 0.0361 in the short janghka. While the long janka down 0.1575. Effect of the domestic price level comparisons and abroad (P) ratio of the price level has a relationship that p [ositif which means if the difference in the price level increases by 1 unit then the short-term changes in exchange rates will change for 2381 , 596 points with the assumption of ceteris paribus. In long-term increase of 10,303.645 points. Keyword : Kurs, Rupiah, Autoregresif, Dollar